Interpretation of Drill Stem Test - All-Said Noor, Sarah N. S.; Al-Jawad, Dr. Mohammed S.; Al-Dabaj, Dr. Abdul Aali (Journal of Petroleum Research and Studies, 2014)
The behavior of pressure derivative analysis and pressure build-up analysis expressed and discussed in this paper. Data from the drill-stem test report for field example through closing the vertical well (Build-up period) analyzed using the ECRIN KAPPA software. Build-up analysis used to estimate characterizations of reservoir: permeability, initial pressure and skin factor. Pressure derivative analysis used to know the type of flow regime, reservoir boundaries, wellbore storage and other parameters. IPR compared with the Vogel method by calculating the constants (0.084755, 1.4428*10-3, and -8.5207*10-7) to replace Vogel's equation constants (1.8, 0.2 and 0.8). Abnormal point is located in a single phase region. Its pressure is greater than that of the next point but its production rate is lower than that of the next point. Productivity index calculated depending on the last production rate. Good results are obtained of determination formation properties by using drill-stem test data instead of production test data. Formation damage is recognized from buildup analysis and constant wellbore storage, unit slope and radial flow regime are recognized from pressure derivative analysis.